1985
DOI: 10.1111/j.1475-2743.1985.tb00666.x
|View full text |Cite
|
Sign up to set email alerts
|

A trial to determine the lime requirement for reseeded grassland on a peaty hill soil

Abstract: Lime was applied in summer 1981 at rates up to 20 t ha-I prior to reseeding an unimproved peaty hill soil. A marked pH gradient with depth developed showing that 3 years after application lime had very little effect below a depth of 5 cm. Soil pH values for 0-7.5 cm samples were: nil lime -4.2; 1 t ha-' -pH 4.3; 2 t ha-' -pH 4.6; 4 t ha-' -pH 5.0; 6 t ha-' -pH 5.6. In the 0-2.5 cm layer pH values were much higher.In all years at least 80% of maximum yield was achieved from an initial application of 2 t ha-' li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
2
8
0
1
Order By: Relevance
“…Changes in the Ah horizon were less marked and only the treatment effect was statistically significant ( pb0.01). The perturbation to the soil chemistry induced by the surface liming treatment was therefore mainly seen in the organic H horizon and almost undetectable in the mineral Ah, a similar finding to previous investigations in uncultivated acid soils (Dampney, 1985).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Changes in the Ah horizon were less marked and only the treatment effect was statistically significant ( pb0.01). The perturbation to the soil chemistry induced by the surface liming treatment was therefore mainly seen in the organic H horizon and almost undetectable in the mineral Ah, a similar finding to previous investigations in uncultivated acid soils (Dampney, 1985).…”
Section: Resultssupporting
confidence: 74%
“…The work was carried out under the UK Natural Environment Research Council's Thematic Programme on Soil Biodiversity and Ecosystem Function which aimed to achieve an understanding of the biological diversity of soil biota and the functional roles played by soil organisms in key ecological processes. The increase in nutrient cycling following liming of acid soils has been well documented (e.g., Floate et al, 1981;Hopkins et al, 1990), although in uncultivated soils, effects on soil chemistry are often limited to the uppermost horizons (Dampney, 1985). Liming also promotes earthworm activity (Springett and Syers, 1984), which may, in turn, affect void space and aggregation.…”
Section: Introductionmentioning
confidence: 97%
“…18,19) Agricultural liming materials increase soil pH, and thereby affect the activity and composition of microbial populations. 20) It has also been found that Ca fertilizers decrease the mobility and consequently also plant availability of Cd, Fe, Mn, and Zn through pH alteration.…”
mentioning
confidence: 99%
“…(Lee et al, 2009;2012). Table 4와 같이, 토 (Dampney, 1985;Tang et al, 2003). 또한 토양 pH의 증가는 microbial biomass 및 효소활성을 촉진시키고, 이는 토양 중 질소 및 인 유효도가 향상될 수 있다 (Cookson, 1999;Tate, 2000;Lee et al, 2008).…”
Section: Introductionunclassified